Challenges for Sustainable Food Systems in Metropolitan Landscapes - Carsjens, G. J. (Agrociencia Uruguay, 2015)
Metropolitan landscapes are facing the challenge to find a balance between urban development on the one hand and the preservation of farmland and natural resources on the other. Conventional land use planning approaches are often not up to this complex challenge and many regions are in need for innovative knowledge and approaches. This paper discusses the role of scenario methodology in the search for innovative solutions, with special emphasis on the challenges related to the sustainability of the food system. An example of application of scenario tools is presented for the Metropolitan Region Amsterdam, the Netherlands.